Redox mechanisms in age-related lung fibrosis - Ashish Kurundkar; Victor J. Thannickal (Redox Biology, 2016)
Redox signaling and oxidative stress are associated with tissue fibrosis and aging. Aging is recognized as a major risk factor for fibrotic diseases involving multiple organ systems, including that of the lung. A number of oxidant generating enzymes are upregulated while antioxidant defenses are deficient with aging and cellular senescence, leading to redox imbalance and oxidative stress. However, the precise mechanisms by which redox signaling and oxidative stress contribute to the pathogenesis of lung fibrosis are not well understood. Tissue repair is a highly regulated process that involves the interactions of several cell types, including epithelial cells, fibroblasts and inflammatory cells. Fibrosis may develop when these interactions are dysregulated with the acquisition of pro-fibrotic cellular phenotypes. In this review, we explore the roles of redox mechanisms that promote and perpetuate fibrosis in the context of cellular senescence and aging.